SAFE, a new therapeutic intervention for families of children with autism: a randomised controlled feasibility trial. Issue 12 (31st December 2020) - McKenzie, Rebecca; Dallos, Rudi; Stedmon, Jacqui; Hancocks, Helen; Vickery, Patricia Jane; Barton, Andy; Vassallo, Tara; Myhill, Craig; Chynoweth, Jade; Ewings, Paul
Abstract : Objectives: To establish the feasibility of a definitive randomised controlled trial of Systemic Autism-related Family Enabling (SAFE), an intervention for families of children with autism. Design: A randomised, controlled, multicentred feasibility study. Setting: Participants were identified from three National Health Service (NHS) diagnosing centres in Plymouth and Cornwall and a community pathway. Participants: 34 families of a child with a diagnosis of autism severity level 1 or 2 between 3 and 16 years. Four families were lost to follow-up. Interventions: SAFE is a manualised five-session family therapy-based intervention delivered over 16 weeks and designed for families of children with autism. SAFE involves families attending five 3-hour sessions led by systemic practitioners. Primary and secondary outcome measures: The proposed primary outcome measure was the Systemic CORE 15 (SCORE-15). Proposed secondary outcome measures: Patient Health Questionnaire-Somatic Anxiety Depressive Symptoms, the Coding of Attachment-Related Parenting for use with children with Autism, the Child Behaviour Checklist (CBCL), the Reflective Functioning Questionnaire (RFQ) and the Caregiving Helplessness Questionnaire. Outcome measures were collected at baseline and 24 weeks post randomisation. Results: All primary caregivers retained in the study completed the SCORE-15 at both time points. 34 of the target of 36 families were recruited and 88% of families were retained. Training for therapists was effective. Feedback revealed willingness to undergo randomisation. There was 100% attendance at appropriate sessions for core family members. The SCORE-15 showed reduction in scores for families receiving SAFE compared with controls suggesting positive change. Qualitative data also revealed that families found the study acceptable and families receiving SAFE experienced positive change. Feedback indicated that the SCORE-15 should be retained as a primary measure in a future trial, but secondary measures should be reduced. Conclusions: This study indicates that a larger trial of SAFE is feasible. Findings suggest that SAFE can address current gaps in recommended care, can be confidently delivered by NHS staff and has potential as a beneficial treatment. Trial registration numbers: ISCTRN83964946 and IRAS213527.